Diversity of teiid lizards from Gran Chaco and Western Cerrado (Squamata: Teiidae). (22nd February 2018) - Arias, Federico José; Recoder, Renato; Álvarez, Blanca Beatriz; Ethcepare, Eduardo; Quipildor, Matias; Lobo, Fernando; Rodrigues, Miguel Trefaut
Abstract : The Gran Chaco dry forest ecoregion corresponds to the southern portion of the South America diagonal belt of open formations, being one of the most threatened subtropical woodland savannas in the world. The area is still poorly known biologically and has been suffering with impressively high forest cover loss in the last 10 years. Integrating morphological and molecular data, we detected and describe a cryptic new species of lizard genus Ameivula endemic from the eastern part of this ecoregion, the called Humid Chaco. Ameivula apipensis sp nov. is characterised by a whitish brown vertebral stripe in adults and juveniles, a lateral field without ocelli and with overlapping spot, presence of an interfrontoparietal scale in 46.2% of the specimens, 12–17 femoral pores, an hemipenis without lateral sac, five xiphisternal ribs, and by a combination of meristic features as confirmed by discriminant analysis. The new species was recovered sister to a clade from Western Cerrado in our analysis, the first phylogenetic hypothesis for the Ameivula and Glaucomastix genera based on 1977 base pairs of three mitochondrial (12S, 16S and cyt‐ b ) and one nuclear (c‐mos) genes, including all the recognised species at the moment. Maximum parsimony and Bayesian inference recovered the monophyly of Ameivula and Glaucomastix with strong support. Reinforcing previous studies, our results suggest the presence of additional cryptic species in Ameivula from the Western Cerrado.